Dose-dependent onset and cessation of action of inhaled budesonide on exhaled nitric oxide and symptoms in mild asthma. Issue 10 (1st October 2002) - Kharitonov, S A; Donnelly, L E; Montuschi, P; Corradi, M; Collins, J V; Barnes, P J
Abstract : Background: Dose dependent anti-inflammatory effects of inhaled corticosteroids in asthma are difficult to demonstrate in clinical practice. The anti-inflammatory effect of low dose inhaled budesonide on non-invasive exhaled markers of inflammation and oxidative stress were assessed in patients with mild asthma. Methods: 28 patients entered a double blind, placebo controlled, parallel group study and were randomly given either 100 or 400 μg budesonide or placebo once daily, inhaled from a dry powder inhaler (Turbohaler), for 3 weeks followed by 1 week without treatment. Exhaled nitric oxide (NO), exhaled carbon monoxide (CO), nitrite/nitrate, S-nitrosothiols, and 8-isoprostanes in exhaled breath condensate were measured four times during weeks 1 and 4, and once a week during weeks 2 and 3. Results: A dose-dependent speed of onset and cessation of action of budesonide was seen on exhaled NO and asthma symptoms. Treatment with 400 μg/day reduced exhaled NO faster (–2.06 (0.37) ppb/day) than 100 μg/day (–0.51 (0.35) ppb/day; p<0.01). The mean difference between the effect of 100 and 400 μg budesonide was –1.55 ppb/day (95% CI –2.50 to –0.60). Pretreatment NO levels were positively related to the subsequent speed of reduction during the first 3–5 days of treatment. Faster recovery of exhaled NO was seen after stopping treatment with budesonide 400 μg/day (1.89 (1.43) ppb/day) than 100 μg/day (0.49 (0.34) ppb/day, p<0.01). The mean difference between the effect of 100 and 400 μg budesonide was 1.40 ppb/day (95% CI –0.49 to 2.31). Symptom improvement was dose-dependent, although symptoms returned faster in patients treated with 400 μg/day. A significant reduction in exhaled nitrite/nitrate and S-nitrosothiols after budesonide treatment was not dose-dependent. There were no significant changes in exhaled CO or 8-isoprostanes in breath condensate. Conclusion: Measurement of exhaled NO levels can indicate a dose-dependent onset and cessation of anti-inflammatory action of inhaled corticosteroids in patients with mild asthma.